VIABILITAS Lactobacillus plantarum 1 YANG DIISOLASI DARI INDUSTRI PENGOLAHAN PATI SAGU TERHADAP GARAM EMPEDU - Darma Lusvina Simbolon; Yusmarini '; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Properties needed for potentially isolates as probiotics should ideally not only able to survive through the digestive tract but also have the ability to reproduce in the digestive tract. The porpuse of the research was to obtain viability of Lactobacillus plantarum 1 strains isolated from processing industry sago starch on bile salts. This research used isolates Lactobacillus plantarum 1           RN2-53, Lactobacillus plantarum 1 RN2-12112, Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 on medium with          oxgall 0,5%. Lactobacillus plantarum 1 RN2-53, L. plantarum 1 RN2-12112 were able to survive in the medium with oxgall 0,5% during incubation for 5 hours. Lactobacillus plantarum 1 RN2-53, L. plantarum 1 RN2-12112 potentially to be used as a candidate of probiotic. Keywords: viability, Lactobacillus plantarum 1, oxgall